Results on stellar occultations by (307261) 2002 MS4 - Rommel, Flavia Luane (2020)
Transneptunian Objects (TNOs) are the remnants of our planetary system and can retain information about the early stages of the Solar System formation. Stellar occultation is a groundbased method used to study these distant bodies which have been presenting exciting results mainly about their physical properties. The big TNO called 2002 MS4 was discovered by Trujillo, C. A., & Brown, M. E., in 2002 using observations made at the Palomar Observatory (EUA). It is classified as a hot classical TNO, with orbital parameters a = 42 AU, e = 0.139, and i = 17.7º. Using thermal measurements with PACS (Herschel) and MIPS (Spitzer Space Telescope) instruments, Vilenius et al. 2012 obtained a radius of 467 +/- 23.5 km and an albedo of 0.051.Predictions of stellar occultations by this body in 2019 were obtained using the Gaia DR2 catalogue and NIMA ephemeris (Desmars et al. 2015) and made available in the Lucky Star web page (https://lesia.obspm.fr/lucky-star/). Four events were observed in South America and Canada. The first stellar occultation was detected on 09 July 2019, resulting in two positives and four negatives chords, including a close one which proven to be helpful to constrain the body’s size. This detection also allowed us to obtain a precise astrometric position that was used to update its ephemeris and improve the predictions of the following events. Two of them were detected on 26 July 2019, separated by eight hours. The first event was observed from South America and resulted in three positive detections, while the second, observed from Canada, resulted in a single chord. Another double chord event was observed on 19 August 2019 also from Canada.